An Examination of The Design Process of Indonesian Architects Through The Lens of Design Theory - H. Wibowo, Danang; Prijotomo, Josef; Saliya, Yuswadi (MAJ - Malaysia Architectural Journal, 2023)
In research on several professional architects, it was found that architects in the design process did not always use linear processes such as analysis, synthesis, and evaluation (Darke, 1979). How professional architects think and process when designing is the subject of discussion. This paper is a study on normative attitudes, methods, strategies, stages, and others related to the design process, with a case study of two female architects, namely Wendy Djuhara and Osrithalita Gabriella. These two women architects are part of the phenomenon of the rapidly growing number of women architects in many countries in the world, including Indonesia in the last 20 years. This study uses a descriptive qualitative approach with narrative nuances. Primary data is obtained through interviews, therefore the analysis method used is qualitative text data analysis. As an instrument of analysis, it uses Rowe’s (1991) premise on normative attitude as a Professional architect and 3 (three) theories of designing from Jones (1970), Broadbent (1977), and Lawson (2005). The objectives of this study are 1) To reveal what kind of normative attitude both of them have as professional architects. 2) How is the designing process of both architects in the selected architectural works? 3) Finding the common thread of the designing process done by the two female architects. The result of this study will be beneficial for the enrichment of Architecture science, as well as the world of Architecture education, especially for students, and Architecture researchers who can use this research as a foundation for other research. This study is also believed to be important for practicing architects because it can add insight as well as alternatives in carrying out the process of designing architecture.